Distrust towards social media influencers : causes and contribution of user’s age, gender and social media use - Hautala, Miriam (2019)
The question of whom to trust or distrust has become an increasingly important aspect in social online networks. As a user encounters much user-generated content each day, evaluating trustworthiness has become continuous. However, distrust and especially distrust in online context has not been studied as much as trust.